Witnessing as an Existential Phenomenon - Ciocan, Cristian (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2023)
In this article, I propose an exploration of the phenomenon of testimony. I argue that the phenomenological viewpoint makes possible an integrative approach to testimony, understood as a phenomenon that engages the entire existential structure of the subject, articulating the relations between language, presence, memory, truth, and temporality. The witness is not only the one who testifies, but first of all the one who faces, in experiential presence, an event whose meaning is overwhelming and thereby institutes the subject as a witness : either as an “enduring witness” if what is at stake is primarily the ownmost self of the witness as such, or as an “eyewitness” if what is at stake is mainly the other. Testimony displays its peculiar significance in the tension between the ontological pole, where the witness is understood as “being there” in the presence of the event on the experiential level, and the hermeneutical pole, where the witness is summoned in front of the others on the level of language. A further difference should be traced between a “confessing-witness,” when the testimony concerns precisely what the witness endured, and the “third-party witness,” whose bearing witness concerns what one mainly observed without enduring it oneself.